SAT0343 BURDEN OF DISEASE AT TREATMENT INITIATION AMONG BIOLOGIC-NAVE PATIENTS WITH OLIGOARTICULAR VERSUS POLYARTICULAR PSORIATIC ARTHRITIS IN THE CORRONA PSORIATIC ARTHRITIS/SPONDYLOARTHRITIS REGISTRY. (June 2019) - Ogdie, Alexis; Liu, Mei; Glynn, Meghan; Emeanuru, Kelechi; Harrold, Leslie; Richter, Sven; Guerette, Benoit; Mease, Philip J.
Abstract : Background: Oligoarticular PsA accounts for ≈50% of PsA worldwide, but only a paucity of data describes disease burden among patients with this subtype. The Corrona PsA/SpA Registry, a prospective, US-based, observational cohort study, collects real-world data on characteristics and treatment of PsA patients, including those with oligoarthritis. Objectives: To characterize demographics, clinical characteristics and patient-reported outcomes (PROs) at treatment initiation in biologic-naïve patients with oligoarticular (≤4 swollen and ≤4 tender joints) vs. polyarticular (>4 swollen or >4 tender joints) PsA. Methods: Biologic-naïve patients ≥18 years of age diagnosed with PsA and enrolled in the registry who initiated apremilast, biologics and/or csDMARDs for PsA from March 2013–December 2018 were included. Data on patient demographics, disease activity, treatment history, comorbidities and PROs were analyzed at treatment initiation; comparisons between oligoarticular and polyarticular PsA patients were performed using t -tests or Wilcoxon rank-sum tests for continuous variables and chi-square tests or Fisher's exact tests for categorical variables, as appropriate. Results: 330 biologic-naïve PsA patients initiating apremilast, biologics and/or csDMARDs were included (oligoarthritis: n=149; polyarthritis: n=181). Demographics and clinical characteristics were mostly similar for patients with oligoarthritis and polyarthritis, including mean age (51.6 vs. 54.3 years; P =0.068), proportion of females (51.0% vs. 59.7%; P =0.117), mean disease duration (3.0 vs. 3.1 years; P =0.789) and prior use of csDMARDs (13.4% vs. 21.0%; P =0.072). History of comorbidities was similar between the 2 groups, but the proportion of patients with fibromyalgia was higher in the polyarthritis group (2.0% vs. 8.8%; P = 0.008; Table 1 ). Patients with oligoarthritis had lower disease activity at treatment initiation vs. those with polyarthritis based on SJC (0-66) and TJC (0-68), nail psoriasis VAS score, cDAPSA score, presence of enthesitis, SPARCC enthesitis score, presence of dactylitis and dactylitis count. More patients with oligoarthritis were classified with minimal disease activity vs. patients with polyarthritis (Table 2 ). Mean Pain VAS (42.6 vs. 59.8), Fatigue VAS (41.9 vs. 55.3), Patient's Global Assessment of Disease Activity VAS (38.6 vs. 47.7) and HAQ-DI (0.7 vs. 1.0) scores were significantly lower and the proportion of patients with HAQ-DI score <0.5 was significantly greater for patients with oligoarthritis vs. polyarthritis (39.7% vs. 20.1%) (all P ≤0.001). Presence of inflammatory back pain (8.7% vs. 10.5%; P =0.588) and mean psoriasis-involved body surface area (8.0% vs. 6.8%; P =0.276) were similar in the 2 groups. Conclusion: This Corrona PsA/SpA Registry analysis showed similar overall disease burden and comorbidity burden in biologic-naïve patients with oligoarthritis and polyarthritis. However, patients with oligoarthritis vs. polyarthritis had lower scores on disease activity and PRO measures at treatment initiation. Acknowledgement: This study was sponsored by Corrona, LLC. Corrona is supported through contracted subscriptions with multiple pharmaceutical companies. The abstract was a collaborative effort between Corrona and Celgene with financial support provided by Celgene. Disclosure of Interests: Alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer Inc, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Mei Liu Employee of: M. Liu is an employee of Corrona, LLC., Meghan Glynn Employee of: M. Glynn is an employee of Corrona, LLC., Kelechi Emeanuru Employee of: Corrona, LLC, Leslie Harrold Shareholder of: Corrona, Grant/research support from: Pfizer, Consultant for: AbbVie, BMS, and Genentech, Employee of: Corrona, Sven Richter Employee of: Celgene Corporation, Benoit Guerette Employee of: Celgene Corporation, Philip J Mease Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Consultant for: AbbVie, Amgen, BMS, Galapagos, Gilead Sciences, Inc., Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Genentech, Janssen, Lilly, Novartis, Pfizer and UCB